Diksyunaryo Filipino-English - Ferrer, Alicia S. (MECS Pub. House, 2003)
This dictionary is intended to help those who want to broaden their knowledge in terms of Filipino language. It can also help the public in anyway it can. If you notice we still borrow English terms and from different languages which only shows that we still don't have any standardization in our Filipino language.